Fully covered metal stents vs plastic stents for preoperative biliary drainage in patients with resectable pancreatic cancer without neoadjuvant chemotherapy: A multicenter, prospective, randomized controlled trial. (11th December 2021) - Mandai, Koichiro; Tsuchiya, Takayoshi; Kawakami, Hiroshi; Ryozawa, Shomei; Saitou, Michihiro; Iwai, Tomohisa; Ogawa, Takahisa; Tamura, Takashi; Doi, Shinpei; Okabe, Yoshinobu; Chiba, Yasutaka; Itoi, Takao
Abstract: Background/Purpose: Whether a fully covered self‐expanding metal stent (FCSEMS) or plastic stent (PS) is preferable for preoperative biliary drainage in patients with resectable pancreatic cancer (RPC) is controversial. This study aimed to evaluate the safety and efficacy of drainage with FCSEMS for obstructive jaundice caused by RPC without neoadjuvant chemotherapy. Methods: Seventy patients with RPC who required preoperative biliary drainage were randomly assigned 1:1 to the FCSEMS or PS group. The primary endpoint was endoscopic re‐intervention rate during the waiting period for surgery. Secondary endpoints were drainage procedure time, drainage‐related adverse events (AE), waiting period for surgery, operative time, intraoperative blood loss, surgery‐related AE, and postoperative hospital stay. Results: Thirty‐nine patients underwent surgery. None required re‐intervention in the FCSEMS group, whereas five PS patients underwent re‐intervention ( P = .023). The FCSEMS group had significantly more intraoperative blood loss ( P = .0068) and AE ( P = .011) than the PS group. Postoperative hospital stay was significantly longer in the FCSEMS group ( P = .016). Conclusions: Fully covered self‐expanding metal stent had a lower rate of endoscopic re‐intervention during the waiting period for surgery than PS, but showed more intraoperative blood loss, higher incidence of surgery‐related AE, and longer postoperative hospital stays.